2009
DOI: 10.1021/ac901100e
|View full text |Cite
|
Sign up to set email alerts
|

Application of Lead and Strontium Isotope Ratio Measurements for the Origin Assessment of Uranium Ore Concentrates

Abstract: Lead and strontium isotope ratios were used for the origin assessment of uranium ore concentrates (yellow cakes) for nuclear forensic purposes. A simple and low-background sample preparation method was developed for the simultaneous separation of the analytes followed by the measurement of the isotope ratios by multicollector inductively coupled plasma mass spectrometry (MC-ICPMS). The lead isotopic composition of the ore concentrates suggests applicability for the verification of the source of the nuclear mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(61 citation statements)
references
References 25 publications
2
57
0
2
Order By: Relevance
“…Švedkauskaitė-LeGore (2007) found that radiogenic Pb isotope abundance ratios vary significantly between different U mines. Subsequent work revealed that Pb isotope ratios could be used in conjunction with trace elemental impurities to distinguish between UOC samples of differing origins (Švedkauskaitė-LeGore 2008), although Varga et al (2009) urged caution in the use of Pb isotope ratios as a signature for UOCs because of substantial withinmine variability. These authors also observed dilution of the intrinsic radiogenic lead signature of the ore by common lead during processing, in some samples to the extent that no radiogenic lead signature remained after processing.…”
Section: Lead Strontium and Neodymium Isotopesmentioning
confidence: 99%
See 3 more Smart Citations
“…Švedkauskaitė-LeGore (2007) found that radiogenic Pb isotope abundance ratios vary significantly between different U mines. Subsequent work revealed that Pb isotope ratios could be used in conjunction with trace elemental impurities to distinguish between UOC samples of differing origins (Švedkauskaitė-LeGore 2008), although Varga et al (2009) urged caution in the use of Pb isotope ratios as a signature for UOCs because of substantial withinmine variability. These authors also observed dilution of the intrinsic radiogenic lead signature of the ore by common lead during processing, in some samples to the extent that no radiogenic lead signature remained after processing.…”
Section: Lead Strontium and Neodymium Isotopesmentioning
confidence: 99%
“…These authors also observed dilution of the intrinsic radiogenic lead signature of the ore by common lead during processing, in some samples to the extent that no radiogenic lead signature remained after processing. Varga et al (2009) applied a common lead subtraction to constrain the radiogenic Pb isotopic composition of the ore. Using this radiogenic Pb isotopic composition, it is possible to calculate an age of the U ore deposit, although this approach is viable only if the radiogenic Pb signal is strong relative to the common lead signature.…”
Section: Lead Strontium and Neodymium Isotopesmentioning
confidence: 99%
See 2 more Smart Citations
“…To-date, much effort has focused on techniques, such as trace element and isotopic analysis, which have demonstrated the ability to link material to a likely geological source [2] [3]. Considerably less effort has been put forth in developing techniques to determine the chemical process history of nuclear materialsalso a desirable outcome of technical nuclear forensics.…”
Section: Introductionmentioning
confidence: 99%